Thomas Hobbes: liberal illiberal - Malcolm, N (British Academy, 2016)
Thomas Hobbes (1588–1679) has often been regarded as a very illiberal thinker —a defender of ‘despotism’ and an advocate of the principle that ‘might is right’. While those accusations are false, it is true that there are distinctly illiberal elements in his thinking. These include absolutism, authoritarianism, anti-constitutionalism and a hostility to democracy. Yet his political theory also contains some of the most important building-blocks of modern liberal thinking about the state and its citizens: the crucial role of consent; natural rights; egalitarianism; the idea of the state as a device to protect people against oppressors; the homogeneity of legal authority within the state; the concept of the state as a public realm; and the idea that the sovereign acts publicly—above all, through law. (These last three points are preconditions of a Rechtsstaat.) And whilst Hobbes denies that people are ruled by a constitution, his theory does acknowledge the need for rule through a constitution.